Relationship between children's theory of mind and metalinguistic competence in early childhood - Kaja Hacin (Psihološka Obzorja, 2016)
The aim of this study was to examine the relations between the theory of mind and metalinguistic competences in early childhood. The sample included 45 children aged from 4;6 to 6 years from 5 different Slovene preschools. The False belief task and the Pictures sequencing task were used to assess children's theory of mind. Children's metalinguistic competences were assessed with the Little glove storytelling test and the Scales of general language development. Children's parents also completed a questionnaire, designed to obtain information about children's play. The results showed significant correlations between children's scores on the majority of tasks. A significant relationship was found between children's theory of mind, their metalinguistic awareness and their storytelling competence, especially the content structure of their story. This association might reflect similar demands for children's understanding of representations that is necessary for the theory of mind and metalinguistic competences. Furthermore, there was no significant correlation between the scores on the Picture sequencing task and children's false belief understanding, but there was a significant correlation between these scores and children's scores on the tasks of metalinguistic competences, which could be an indicator of a relation between child's sequencing of pictures into a complete story and their metalinguistic competences. Results did not show significant differences between children's theory of mind or their metalinguistic awareness based on the type of their most frequent play. Thus, the study provides a complex insight into relations between different aspects of children's theory of mind and metalinguistic competences; and as such highlights the strong relationship between both constructs.